The mediating role of resilience in the effects of physical exercise on college students’ negative emotions during the COVID-19 epidemic - Li, Xuening; Yu, Huasen; Yang, Ning (Scientific reports, 2021)
Due to its suddenness and unpredictability, COVID-19 caused strife and effects on public mental health, resulting in a surge of negative emotions. The study explores the relationship between physical exercise and negative emotions in home-based college students during the COVID-19 epidemic, as well as the mediating role of resilience, thus providing a new basis for understanding the role of physical exercise in improving negative emotions in college students; A total of 1214 college students were investigated with the Physical Exercise Questionnaire, Negative Emotion Scale and Resilience Scale; Both physical exercise and resilience were significantly negatively correlated with negative emotions in college students (r = − 0.25, − 0.33, P < 0.001), and there was a significant positive correlation between physical exercise and resilience (r = 0.47, P < 0.001). Physical exercise had a direct effect on the negative emotions of college students (β = − 0.14, P < 0.001). Resilience had a partial mediating effect between physical exercise and the negative emotions of the college students, with a mediating effect value of 0.14 and a mediating effect contribution rate of 50.00%; The study found that physical exercise not only directly affected the negative emotions of college students but also improved their resilience by slowing down their negative emotions and promoting their mental health.